Hierarchical 3D Fe-doped Bi2MoO6 arrays supported on a Ni foam: an effective electrocatalyst for alkaline water splitting - Singh, Dinesh; Poddar, Pankaj (Nanoscale, 2026)
Electrocatalytic water splitting is a viable route to sustainable hydrogen generation; however, designing high-performance, stable catalysts remains a considerable challenge. Bismuth-based materials have not yet been well studied for electrocatalytic alkaline water splitting, despite their favourable electronic structure and chemical stability. Here, iron-doped hierarchical three-dimensional (3D) Bi2MoO6 arrays have been grown in situ on a 3D conductive nickel foam (NF) substrate using a facile solvothermal method. The optimal Fe-doped Bi2MoO6/NF (Fe, 5 mol% substituting Bi) or BMOF-5 electrocatalyst exhibits excellent electrocatalytic activity towards the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline media (pH similar to 14.0) owing to abundant active sites in the hierarchical 3D framework, high electrical conductivity, and superhydrophilic nature. At a current density of 10 mA cm-2, the BMOF-5 electrocatalyst requires 262 mV and 153 mV overpotentials for the OER and HER, respectively. In addition, a potential of 1.62 V is required by the BMOF-5/NF parallel to BMOF-5/NF cell at a current density of 10 mA cm-2 for overall water splitting. The BMOF-5/NF electrocatalyst shows durability of 24 h and 22 h for the HER and OER in a 1 M KOH electrolyte at current densities of 100 and 10 mA cm-2, respectively. In this study, a small amount of iron plays an important role in altering the electronic environment of Bi2MoO6, increasing the electrochemically active sites and reducing the charge-transfer resistance at the electrode-electrolyte interface. In addition, this work presents an easy and efficient approach to enhance the electrocatalytic performance of Bi2MoO6, which is of significant practical importance.